AN EVALUATION OF CHILDREN'S PERFORMANCE ON CERTAIN COGNITIVE, AFFECTIVE, AND MOTIVATIONAL ASPECTS OF THE INTERACTION UNIT OF THE SCIENCE CURRICULUM IMPROVEMENT STUDY ELEMENTARY SCIENCE PROGRAM. - Allen, Leslie R. (Journal of Research in Science Teaching, 1972)
The article investigates whether participation in the Science Curriculum Improvement Study (SCIS) elementary science program by children at the grade two level results a superior performance in the U.S. The SCIS grade 2 Physical Science Interaction unit teaches the concept of systems, interaction, and evidence of interaction. The SCIS Grade 2 program appears to be satisfactorily meeting some of its own objectives. It shows that 90 percent of the SCIS children tested understood and were able to respond to questions involving the term interact and evidence of interaction.